Bioactive 3D-printed chitosan-based scaffolds for personalized craniofacial bone tissue engineering - Satar Yousefiasl; Esmaeel Sharifi; Erfan Salahinejad; Pooyan Makvandi; Soussan Irani (Engineered Regeneration, 2023)
Regeneration of craniofacial bone defects is a key issue in the bone regeneration field. Hence, novel treatment strategies, such as tissue engineering using porous scaffolds, have been developed. An ideal tissue-engineered scaffold for bone tissue regeneration should possess pores to facilitate nutrients transmission and support reparative tissue ingrowth, bioactivity for osteoconduction and osseointegration, and biocompatibility to improve cell attachment, proliferation, and extracellular matrix formation. In the present study, we manufactured chitosan-based hydrogels substituted with alginate with optimized properties by extrusion-based three-dimensional (3D) printing. 3D printing of the scaffolds enables the designing and developing of complex architectures for craniofacial reconstruction using computer-aided design (CAD). Different ratios (2.5, 5, and 10%) of hydroxyapatite were added to the hydrogel, printed, and subsequently lyophilized to augment the physical and biological characteristics of the scaffolds. Hydroxyapatite incorporation into the chitosan-based scaffolds increased the porosity and pore size of the printed scaffolds. In addition, the presence of hydroxyapatite amplified apatite formation and decreased the size of formed apatite crystals. All the scaffold samples showed biocompatible properties and did not have toxicity toward rat bone marrow mesenchymal stem cells. Furthermore, the scaffolds containing 5% w/w hydroxyapatite exhibited significant growth in cell viability compared to the control. Overall, it is concluded that chitosan-based scaffolds adorned with hydroxyapatite are considerable for regenerating craniofacial bone defects.